Retention of Microbiota Diversity by Lactose-Free Milk in a Mouse Model of Elderly Gut Microbiota - Ntemiri, Alexandra; Ribière, Céline; Stanton, Catherine; Ross, R. Paul; O’Connor, Eibhlís M; O’Toole, Paul W (Journal of agricultural and food chemistry, 2019)
Prebiotics may improve aging-related dysbiosis. Milk is a source of nutrients including oligosaccharides whose prebiotic potential remains largely unexplored. We used a murine model to explore the effect of milk products on high diversity and lower diversity faecal microbiota from healthy and frail elderly subjects, respectively. Mice were treated with antibiotics and subsequently “humanized” with human faecal microbiota. The mice received lactose-free or whole milk, glycomacropeptide, or soy protein (control) supplemented diets for one month. The faecal microbiota was analyzed by 16S rRNA gene amplicon sequencing. Lactose-free milk diet was as efficient as the control diet in retaining faecal microbiota diversity in mice. Both milk diets had a significant effect on the relative abundance of health-relevant taxa (e.g., Ruminococcaceae, Lachnospiraceae). The glycomacropeptide prebiotic activity previously observed in vitro was not replicated in vivo. However, these data indicate the novel prebiotic potential of bovine milk for human nutrition.